Aldolase A Promotes Colorectal Cancer Progression through Targeting COPS6 and Regulating MAPK Signaling Pathway - Lu, Ya; Zhang, Yuan; Wang, Xinyue; Zhang, Hui; Zhu, Yue; Zhang, Junying; Sha, Huanhuan; Zou, Renrui; Gan, Yujie; Sui, Ying; Wang, Juan; Du, Tongde; et al. (Disease Markers, 2023)
Colorectal cancer (CRC) is a serious threat to human health, and its underlying mechanisms remain to be further explored. Aldolase A (ALDOA) has received increasing attention for its reported association with multiple cancers, but the role and mechanisms of ALDOA in CRC are still unclear. In the current study, high expression levels and enzymatic activity of ALDOA were detected in CRC tissues and cell lines, indicating the clinical significance of ALDOA in human CRC. In addition, silencing ALDOA significantly impaired the proliferation and metastasis of CRC cells in vitro and in vivo. Mechanistically, immunoprecipitation assays and mass spectrometry analysis identified the binding protein COPS6 of ALDOA. Furthermore, the promoting effects of upregulated ALDOA on CRC cell proliferation and metastasis were inhibited by COPS6 depletion, demonstrating COPS6 was required for ALDOA in mediating CRC progress. Moreover, the epithelial-mesenchymal transition (EMT) program and MAPK signaling pathway were found to be activated by ALDOA overexpression as well. In summary, our findings suggested that ALDOA facilitated the proliferation and metastasis of CRC by binding and regulating COPS6, inducing EMT, and activating the mitogen-activated protein kinase (MAPK) signaling pathway. The present study provided evidence for ALDOA as a promising potential biomarker for CRC.